2012
DOI: 10.5641/027013612804582669
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Pregnancy: Past and Present Evidence and Future Recommendations

Abstract: Purpose This review provides researchers and practitioners with an overview of the physical activity and pregnancy literature to promote prenatal physical activity, improve measurement, further elucidate the role of activity in reducing maternal health complications, and inform future research. Methods We examined past and present physical activity and pregnancy studies and highlight key papers with a particular focus on maternal health outcomes to best inform physical activity promotion efforts. Results T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 117 publications
(168 reference statements)
2
69
0
4
Order By: Relevance
“…The results of many studies confirm the positive effect of physical activity during pregnancy on the health of both mother and child [1]. Increased physical activity in pregnant women in conjunction with a proper diet was connected with a lower risk of excessive weight gain in pregnancy, cesarean delivery, macrosomia, and neonatal respiratory morbidity [2], had a positive effect on the concentration of cholesterol, C-reactive protein (CRP), and blood pressure [3], and reduced the risk of preeclampsia [4] and gestational diabetes [5].…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…The results of many studies confirm the positive effect of physical activity during pregnancy on the health of both mother and child [1]. Increased physical activity in pregnant women in conjunction with a proper diet was connected with a lower risk of excessive weight gain in pregnancy, cesarean delivery, macrosomia, and neonatal respiratory morbidity [2], had a positive effect on the concentration of cholesterol, C-reactive protein (CRP), and blood pressure [3], and reduced the risk of preeclampsia [4] and gestational diabetes [5].…”
Section: Introductionmentioning
confidence: 56%
“…In the authors' opinion, the PPAQ can be used to determine the lower and upper levels of rigor (intensity, duration, frequency) for activity during pregnancy, and to identify the specific parameters that characterise both threshold and dose response effects for investigations of physical activity and foetal and maternal outcomes [17]. The usefulness of the questionnaire for the assessment of physical activity in pregnant women should be emphasised especially in relation to the great need for further studies on the impact of physical activity and sedentary behaviour of pregnant women on the risk of adverse health effects for infants and mothers in their later life [1].…”
Section: Discussionmentioning
confidence: 99%
“…Whereas there is ample research regarding the outcomes of physical activity during pregnancy, little research exists regarding the effects of pregravid physical activity on maternal and infant birth outcomes [8]. For example, one study that examined pre-pregnancy physical activity found that women who engaged in vigorous activity or brisk walking prior to pregnancy were less likely (but not statistically significant) to develop gestational diabetes [9].…”
Section: Introductionmentioning
confidence: 97%
“…16---20 In addition, the majority of the successful interventions to date have been conducted in predominantly White non-Hispanic study populations or have used intensive interventions that may not be feasible in clinical practice. 21 Individually tailored, motivationally matched interventions have been shown to be cost-effective approaches to increasing physical activity in nonpregnant women in community settings. 22,23 These interventions are also readily translatable to clinical practice.…”
mentioning
confidence: 99%